Betonarme köprülerde sismik izolasyon etkisinin incelenmesi ve bir uygulama örneği - Mum, Nusret (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / İnşaat Mühendisliği Anabilim Dalı / Yapı Bilim Dalı, 2006)
In this era of technological revolution, the world of seismic engineering is in need of creative thinking and advanced technologies beyond conventional solutions. Seismic isolation is the best available technology for seismic protection of a variety of infrastructures that have the requisite dynamic characteristics. The ability of the isolation system to dissipate energy in a controlled and non-degrading manner makes it consistent with contemporary thinking in seismic engineering. Isolation technology has matured in recent years to a highly dependable and reliable level. Practical application of seismic isolation in a variety of building projects is technically and economically feasible. Seismic isolation has been successfully installed in many new and several seismic retrofit projects. Design of isolated buildings, viaducts, etc. requires attention to many unique issues that affect the overall building design. This study investigates the effect of installing rubber isolators in places of the bridges supports to reduce earthquake structural responses.
Keywords: ulaşım; inşaat mühendisliği